2019
DOI: 10.1038/s41467-018-07918-z
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-activated Cl− channel TMEM16A/ANO1 identified in zebrafish skeletal muscle is crucial for action potential acceleration

Abstract: The Ca2+-activated Cl− channel (CaCC) TMEM16A/Anoctamin 1 (ANO1) is expressed in gastrointestinal epithelia and smooth muscle cells where it mediates secretion and intestinal motility. However, ANO1 Cl− conductance has never been reported to play a role in skeletal muscle. Here we show that ANO1 is robustly expressed in the highly evolved skeletal musculature of the euteleost species zebrafish. We characterised ANO1 as bonafide CaCC which is activated close to maximum by Ca2+ ions released from the SR during e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 64 publications
(112 reference statements)
1
17
0
Order By: Relevance
“…Our data provide explanation of outward rectification previously observed in wholecell recordings of CaCCs [50]. Both the conductance and the open probability of CaCCs increased at positive potentials (Figure 1).…”
Section: Discussionsupporting
confidence: 87%
“…Our data provide explanation of outward rectification previously observed in wholecell recordings of CaCCs [50]. Both the conductance and the open probability of CaCCs increased at positive potentials (Figure 1).…”
Section: Discussionsupporting
confidence: 87%
“…Rapid activation of TMEM16A can regulate the electrical activity by inducing membrane depolarization or by accelerating action potential repolarization; this has been shown in neurons from dorsal root ganglia, cholinergic neurons of the medial habenula and muscle cells 36,47 . Thus, activation of TMEM16A enables neurons to respond to thermal stimulus, control anxiety-related behaviour 36,47 and increase the frequency of action potentials in skeletal muscle cells of zebrafish 48 . A more direct physiological role for TMEM16A regulation by protons is suggested by its simultaneous activation with H + ATPase in the apical membrane of proximal tubules of mouse kidney 49 .…”
Section: Discussionmentioning
confidence: 99%
“…In our current hypoxia study, two orthologs are found-CLCA1 and CLCA3. Recent studies demonstrated that CLCA1 forms non-covalent oligomers in colonic mucus and has Mucin 2-processing properties, playing an important role in regulating the structural arrangement of the mucus and thereby partly mediating mucus processing (Dayal et al, 2019;Nyström et al, 2019). Few reports are available on the functional analysis of CLCA3.…”
Section: Discussionmentioning
confidence: 99%